Screening of Antibacterial and Antioxidant Activities for Safflower Water Extracts to Increase Immunity During a Pandemic - Amalyah Febryanti; Fitria Azis (Elkawnie: Journal of Islamic Science and Technology, 2022)
Abstract: Viral infection is the multiplication of viruses in the body. Viruses can reproduce with the help of a host. Viruses infect a host by inserting their genetic material into cells to duplicate their particles. Coronavirus is a type of virus. The coronavirus identified in 2019, SARS-CoV-2, has caused a pandemic of the respiratory disease called COVID-19. Screening of the antibacterial and antioxidant activity of safflower aqueous extract has to be carried out to seal immunity against the virus. The purpose of this study was to determine the antibacterial and antioxidant activity of Kasumba turate water extract. The method used in this study was an experiment consisting of the preparation of Staphylococcus aureus suspensions, the preparation of safflower aqueous extract, phytochemical screening of safflower aqueous extract, a study of the functional group of safflower aqueous extract using FTIR, and the determination of antibacterial and antioxidant activities. The results obtained show that the extract has physical characteristics of a brownish yellow color and the characteristic odor of Kasumba turate. A phytochemical study verified that the aqueous extract of safflower contains alkaloids, flavonoids, and tannins. Analyze FTIR for the expected presence of functional groups including -OH, =CO, and -NH. The best antibacterial activity under three conditions was shown at a 5% extract concentration with a solvent heating temperature of 90 ºC for 15 minutes which gave abroad an inhibition zone. Safflower aqueous extract indicated DPPH radical scavenging activity with an IC50 value of 965.33 mg mL-1. Furthermore, safflower aqueous extract has the potential for antioxidant activity, but it has low antibacterial activity. However, this study supports making Safflower a natural colorant in food and recommends using Safflower as a tea or herbal drink that provides natural antioxidant effects during the pandemic.Abstrak: Skrining aktivitas antibakteri dan antioksidan ekstrak air kasumba turate dilakukan. Metode yang digunakan dalam penelitian ini adalah metode eksperimen yang terdiri dari preparasi suspensi Staphylococcus aureus as test bacteria, preparasi ekstrak air kasumba turate, skrining fitokimia ekstrak air kasumba turate, studi gugus fungsi ekstrak air kasumba turate menggunakan FTIR, penentuan aktivitas antibakteri, dan penentuan aktivitas antioksidan. Hasil yang diperoleh menunjukkan bahwa ekstrak memiliki ciri fisik warna kuning kecoklatan dan bau yang khas. Studi fitrokimia membuktikan bahwa ekstrak air kasumba turate mengandung alkaloid, flavonoid, dan tanin. Analisis FTIR diharapkan adanya gugus fungsi yang meliputi -OH, =CO, dan -NH. Aktivitas antibakteri terbaik pada ketiga kondisi ditunjukkan pada konsentrasi ekstrak 5% dengan suhu pemanasan pelarut 90 ºC selama 15 menit yang memberikan zona hambat luas. Ekstrak air safflower menunjukkan aktivitas penangkapan radikal DPPH dengan nilai IC50 1250 mg mL-1. Selain itu, penelitian ini mendukung untuk menjadikan kasumba turate sebagai pewarna alami pada makanan dan merekomendasikan penggunaan kasumba turate sebagai teh atau minuman herbal yang memberikan efek antioksidan alami selama masa pandemi.